2015
DOI: 10.1111/1753-6405.12404
|View full text |Cite
|
Sign up to set email alerts
|

Australian trampoline injury patterns and trends

Abstract: Objectives: To examine national trampoline injury patterns and trends in the context of improved product safety standards and trampoline design modifications. Method: Review of National Hospital Morbidity data. Results: There were an average 1,737 trampoline injuries reported nationally each year from 2002 to 2011. Both injury frequency and rate grew. Statistically significant rate increases were observed among all age groups, although both are highest among children aged 5–9 years. From 2008/09 there is a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 9 publications
5
43
4
Order By: Relevance
“…Trampolines were the most common type of equipment to cause a fall‐related injury overall, particularly for children aged 0–4 and 10–14 years. These findings are corroborated in another study that found trampolines to be a common type of play equipment involved in fall‐related injuries of children . Use of protective features on trampolines such as in‐ground trampolines to minimise fall height, padded edges, and flexible enclosures are recommended to reduce the risk of injury; however, it has been suggested that these features may lead to a false sense of safety and result in less supervision .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Trampolines were the most common type of equipment to cause a fall‐related injury overall, particularly for children aged 0–4 and 10–14 years. These findings are corroborated in another study that found trampolines to be a common type of play equipment involved in fall‐related injuries of children . Use of protective features on trampolines such as in‐ground trampolines to minimise fall height, padded edges, and flexible enclosures are recommended to reduce the risk of injury; however, it has been suggested that these features may lead to a false sense of safety and result in less supervision .…”
Section: Discussionmentioning
confidence: 67%
“…These findings are corroborated in another study that found trampolines to be a common type of play equipment involved in fall-related injuries of children. 31 Use of protective features on trampolines such as in-ground trampolines to minimise fall height, padded edges, and flexible enclosures are recommended to reduce the risk of injury 32 ; however, it has been suggested that these features may lead to a false sense of safety and result in less supervision. 31 Limiting use to one person at any time on a trampoline is also recommended to reduce collisionrelated injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms attributable to injury patterns are not clear in this or in similar studies; in this study it was poorly recorded, mostly documented as ‘awkward landing’. However, it is clear that ITP injuries are less likely than domestic trampoline injuries to be due to a simple fall from the trampoline 2,17 . While the incidence of head and spinal injuries is relatively low, their severity and potential for life‐long impairment justifies a call for mandatory standards to ensure industry compliance towards reducing the injury risk by the maximum extent possible.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,10,39 Probably because of the wall-to-wall trampoline design, there were few falls from trampolines at trampoline parks (Table 2), which may account for the decreased proportion of head and arm injuries at trampoline parks. Lower extremity injuries were common at trampoline parks, and a number of serious lower extremity injuries were reported, including open fractures, dislocations, and other leg fractures necessitating hospital admission.…”
Section: Table 2 Injury Mechanisms Atmentioning
confidence: 99%